31.2k views
1 vote
Add: f(x)+g(x)
f(x) = 2x2 – 3x² + 7x+1
g(x) = 4x2 + 5x +12
Submit

Add: f(x)+g(x) f(x) = 2x2 – 3x² + 7x+1 g(x) = 4x2 + 5x +12 Submit-example-1
User Liedman
by
5.8k points

1 Answer

5 votes

Answer:


f(x) + g(x) = 2x^3 + x^2 + 12x + 13

Explanation:

We are given these following functions:


f(x) = 2x^3 - 3x^2 + 7x + 1


g(x) = 4x^2 + 5x + 12

Add: f(x)+g(x)

To add them, we combine the like terms. So


f(x) + g(x) = 2x^3 - 3x^2 + 7x + 1 + 4x^2 + 5x + 12 = 2x^3 + (-3+4)x^2 + (7+5)x + 1 + 12 = 2x^3 + x^2 + 12x + 13

The added function is:


f(x) + g(x) = 2x^3 + x^2 + 12x + 13

User Hessius
by
6.0k points